Thinking and Dialoguing about Jesus the Jew: A Semiotic Christology - Hoff, Gregor Maria; Cunningham, Philip A. (Studies in Christian-Jewish Relations, 2026)
Semiosis, from the Greek semeion or sign, is how human beings use symbols or signs to make sense of the world and communicate with one another. This essay examines christology and Christian-Jewish relations by underscoring that a language is a symbol system that enables viewers or readers to construct meaning from hearing or reading words. It proposes that the sign “Christ”—as the Christian creation of meaning in relation with the sign “God”—can be (re)constructed to be theologically comprehensible, though not endorsed, from the perspective of Jewishly understood monotheism. This enables the potential for Jews to respect Christian christologies and for Christians to appreciate the Jewish “no” to Christ—while still identifying with their own tradition’s parameters. A “semiotic christology” makes it possible for them to ascribe reasonableness to their differences about Jesus and how they arose and historically developed. The essay also suggests that semiotics can elucidate how Christians and Jews who engage in interreligious dialogue sometimes report that they have been spiritually touched by their exchanges with each other.